Identifying seedling and adult plant resistance of Chinese Brassica napus germplasm to Leptosphaeria maculans. (2nd November 2016) - Zhang, X.; Peng, G.; Parks, P.; Hu, B.; Li, Q.; Jiang, L.; Niu, Y.; Huang, S.; Fernando, W. G. D.
Abstract : Blackleg disease of canola/rapeseed ( Brassica napus ), caused by the devastating fungal pathogen Leptosphaeria maculans, can significantly influence B. napus production worldwide, except for China, where only the less aggressive L. biglobosa has been found associated with the disease. The aim of this study was to characterize both seedling resistance (major gene resistance, R gene resistance) and adult plant resistance (APR) from a collection of Chinese B. napus varieties/lines (accessions) to L. maculans . Evaluation of seedling resistance was carried out under a controlled environment, using 11 well‐characterized L. maculans isolates as differentials. The identification of APR was performed under multiple field environments in western Canada. R genes were detected in more than 40% of the accessions tested. Four specific R genes, Rlm1, Rlm2, Rlm3 and Rlm4 were identified, with Rlm3 and Rlm4 being the most common genes, while Rlm1 and Rlm2 were detected only occasionally. Results of field evaluation indicated significant variations among field locations as well as accessions; a large portion of the B. napus accessions, regardless of the resistance level observed at the seedling stage, showed high to moderate levels of APR under all environments tested. This study highlights that both R gene resistance and APR are present in Chinese B. napus germplasm and could be potential sources of resistance against blackleg caused by L. maculans if the pathogen ever becomes established in China.